The life experience of multiple childhoods and adolescent youth in the Covid-19 pandemic: Dewey and pedagogical practices in the teaching of Visual Arts (Revista Apotheke, 2021)
This article reflects on the life experiences of the Covid-19 pandemic, especially those of children and adolescents. Within the scope of the pandemic, we observed the artistic manifestations raised and the aggravated social vulnerabilities present in childhood and adolescence. We seek to understand these experiences in order to think about Visual Arts Teaching, specifically, its curricular contents, thinking in the context of different childhoods and adolescent youth. Secondly, we discuss Visual Arts Teaching in the face of the pandemic, with support from the perspective of Dewey (2011), in particular, in his chapter entitled 'The progressive organization of curricular subjects and contents'. We use as a methodology the bibliographic review of books, book chapters, articles and electronic sites and consultations on virtual platforms of Visual Arts. We conclude that the pandemic's visualities act as cultural pedagogies and that the Teaching of Visual Arts can encompass the students' life experience, based on content that proposes reflection on the contemporary moment.